High-thixotropy polyurethane composition as well as preparation method and application thereof

Through the combination technology of isocyanate components and isocyanate reactive components, a highly thixotropic polyurethane composition is achieved, which solves the dripping problem during spraying, improves the sag effect and filling performance of the material, and is suitable for the preparation of complex shapes and large-size interlayer materials.

CN119735779AActive Publication Date: 2025-04-01WANHUA CHEM BEIJING +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510000359.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-01
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The existing polyurethane compositions have severe dripping during spraying, resulting in a decrease in raw material utilization and an increase in cost, and there are defects in material defects or defects in complex shapes or large-sized products, affecting the mechanical strength and aesthetics of the product.

Method used

Using the combination technology of isocyanate components and isocyanate reactive components, rapid pre-crosslinking and chain extension reactions are achieved in the early stage of the reaction to obtain a highly thixotropic polyurethane composition. In the state of no pressure, the viscosity is relatively large and has excellent sagging effect; under a certain pressure, the viscosity is greatly reduced, maintaining fluidity for a long time, and promoting surface leveling.

Benefits of technology

The sag effect and filling performance of the polyurethane composition are improved, and the prepared interlayer material has high surface density, excellent filling effect, high aesthetics, and excellent mechanical properties. It is suitable for the preparation of interlayer materials with complex shapes and large sizes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005224807370000121
    Figure BDA0005224807370000121
  • Figure BDA0005224807370000131
    Figure BDA0005224807370000131
  • Figure BDA0005224807370000141
    Figure BDA0005224807370000141
Patent Text Reader

Abstract

The invention discloses a high-thixotropy polyurethane composition as well as a preparation method and application thereof. The polyurethane composition comprises A) an isocyanate component and B) an isocyanate reactive component, wherein the component B) comprises the following components: B1) polycyclic amines; b2) polyether polyol 1, the functionality of which is 2-5 and the hydroxyl value of which is 200-800 mgKOH / g, and the content of ethylene oxide in a polymeric monomer of the polyether polyol 1 is 20-100% based on the total mass of epoxypropane and ethylene oxide; optionally B3) polyether polyol 2 having a functionality of 2-4, a hydroxyl value of 20-170mgKOH / g, and an ethylene oxide content of 0-20%, based on the total mass of propylene oxide and ethylene oxide; and B4) polyether polyol 3 which is formed by polymerizing epoxypropane and has the functionality of 2-4 and the hydroxyl value of 150-600mgKOH / g. The polyurethane composition provided by the invention has high thixotropy, has high viscosity and does not flow in a non-pressure state, and has good fluidity in a pressure state.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyurethane materials, and in particular relates to a high thixotropic polyurethane composition and a preparation method and application thereof. Background Art

[0002] With the rapid development of the automobile industry and the implementation of the national development strategy for new energy electric vehicles, the society's demand for lightweight, low-energy consumption, and high-safety materials is increasing; the production of lightweight composite automotive interior and exterior parts has also become a consensus and the main direction of development in the automotive industry. Therefore, high-strength and lightweight sandwich structure composite materials are being strongly sought after by the market, and domestic and foreign automobile brands have used high-performance engineering plastics and plastic composite materials on a large scale to reduce the weight of automobiles.

[0003] Polyurethane foam can be used in the production of complex shapes and large-sized products due to its advantages such as excellent lightweight, excellent environmental performance, low production cost, and high plasticity. As a new type of foaming material, polyurethane foam is being widely used in wind turbine blades, automotive interior and exterior decoration, building materials, hulls, etc.

[0004] Honeycomb reinforced polyurethane composite structure is a material developed in recent years that can be used for high-performance and lightweight automotive molding. The structure is composed of polyurethane foam, fiber reinforcement and honeycomb composite. The honeycombs used include paper honeycombs, metal honeycombs and plastic honeycombs. This type of reinforced composite structure has the advantages of light weight, high bending strength, good dimensional stability, good environmental performance, high production efficiency and flexible design. Compared with traditional automotive interior and exterior trim structures, its weight can be reduced by 30% under the same stiffness conditions, which meets market demand and greatly saves manufacturing costs. The material also has environmentally friendly characteristics such as flame retardancy, low odor and low emission. It is precisely because the sandwich products formed by polyurethane honeycomb composite molding are beautiful, safe, lightweight, environmentally friendly and low-cost, so they meet the needs of the rapid development of the automotive industry.

[0005] The preparation process of the honeycomb panel sandwich material currently on the market is as follows: the honeycomb structure is used as the core material, and the two sides of the core material are reinforced fiber felt or fiber cloth. The polyurethane composition is sprayed on one side of the reinforced fiber felt or fiber cloth, the fixture is turned over, and the operation is repeated to spray the other side until the double-sided spraying is completed. The product is placed in a mold, and the polyurethane composition is foamed, leveled, cured and demolded in the mold under a certain pressure and temperature.

[0006] At present, conventional polyurethane compositions on the market are sprayed on reinforcing fibers. Since they need to be turned over to spray the other side, the polyurethane raw materials will seriously drip after turning over, resulting in a significant decrease in the utilization rate of the polyurethane raw materials and an increase in costs. At the same time, the dripping polyurethane composition will pollute the environment after foaming, and it needs to be cleaned frequently. More importantly, due to the dripping of the polyurethane composition, the edges or modeling areas of the products cannot be fully filled, especially for large-sized and complex-shaped products, there are serious material shortages or hollow defects, which affect the mechanical strength and aesthetics of the products.

[0007] As described in patent CN110964173A, the patent discloses a preparation of a honeycomb composite polyurethane composition, and the prepared product has low emission and low water absorption; however, the patent has the disadvantages of no rapid viscosity increase effect after the polyurethane composition is mixed, a large amount of dripping will occur during the spraying and flipping process of the raw materials, resulting in insufficient raw material utilization and increased costs, and the product modeling area is prone to incomplete filling, etc.

[0008] In the prior art, the anti-drip effect is also achieved by increasing the mixed viscosity of the polyurethane composition by physical or chemical reaction.

[0009] In terms of physical thickening, powder fillers such as silica and glass beads are usually purchased on the market to increase the initial viscosity of the raw materials. However, due to the high initial viscosity of the raw materials, the mixing requirements of the equipment are very high. At the same time, due to the presence of powders, the storage stability and processability of the raw materials are very poor. In addition, the polyurethane composition is prone to blocking the gun head during the mixing process, resulting in an unstable product production process and a significant increase in the overall cost.

[0010] In terms of chemical thickening, the market mostly uses highly active DETDA to achieve the effect of raw material thickening, which plays a role in preventing dripping during the spraying process. Because DETDA has a fast reaction activity and a high degree of crosslinking in the early stage, the viscosity of the polyurethane composition increases significantly immediately after mixing. Although this method has a good anti-drip effect, the actual production process of the product still requires many operations such as spraying, placing in molds, and closing molds, requiring the polyurethane composition to have a long operation period. However, due to the presence of DETDA, the polyurethane composition instantly undergoes a deep crosslinking reaction, and the fluidity of the raw materials is greatly reduced, which is very unfavorable for the molding of complex or large-sized products. There are often defects such as lack of material, large pinholes, and uneven flow in the molding area. Therefore, this solution is usually only suitable for the production of products with simple shapes and small sizes;

[0011] As described in patent CN101641384B, the patent discloses a polyurethane system for preparing polyurethane sandwich components. Due to the use of highly active chain extender DETDA, the instantaneous viscosity of the polyurethane composition after mixing is greatly improved, achieving a good anti-sagging effect and improving the utilization rate of raw materials; but it is also precisely because of the presence of DETDA that the instantaneous viscosity of the polyurethane composition after mixing is greatly increased, the initial degree of crosslinking of the mixture is already relatively large, and there is no thixotropy, which causes the fluidity of the mixture in the mold to be greatly reduced, which is not conducive to the molding of large-sized and complex-shaped products.

[0012] Therefore, in order to solve the problems existing in the prior art, the present invention provides a highly thixotropic polyurethane composition, which can quickly achieve high thixotropy after mixing an isocyanate component and an isocyanate-reactive component. Under no-pressure conditions, the viscosity is relatively high (apparently non-flowing) and has an excellent sag effect; when the product enters a mold and is subjected to a certain pressure, the viscosity can be greatly reduced, and the fluidity can be maintained for a long time at room temperature and high temperature, promoting surface leveling. The composite sandwich product prepared from the polyurethane composition has high surface density, excellent filling effect, high aesthetics, and excellent mechanical properties; the polyurethane composition is suitable for preparing sandwich materials with complex shapes and large sizes. Summary of the invention

[0013] In order to solve the above technical problems, the present invention provides a highly thixotropic polyurethane composition and a preparation method and application thereof.

[0014] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0015] A highly thixotropic polyurethane composition comprising: A) an isocyanate component, B) an isocyanate reactive component;

[0016] Wherein, component B) comprises the following composition:

[0017] B1) fused cyclic amines having a functionality of 1-6, preferably 2-4;

[0018] B2) polyether polyol 1, having a functionality of 2-5, preferably 3-4, a hydroxyl value of 200-800 mgKOH / g, preferably 400-700 mgKOH / g, and an ethylene oxide content of 20-100%, preferably 60-100%, in the polymerized monomers, based on the total mass of propylene oxide and ethylene oxide;

[0019] Optionally B3) polyether polyol 2, with a functionality of 2-4, a hydroxyl value of 20-170 mgKOH / g, and an ethylene oxide content of 0-20%, based on the total mass of propylene oxide and ethylene oxide;

[0020] Optionally B4) polyether polyol 3, prepared by polymerization of propylene oxide, with a functionality of 2-4 and a hydroxyl value of 150-600 mgKOH / g, preferably 240-500 mgKOH / g.

[0021] In some preferred embodiments, the usage ratio of component A) to component B) is (1.5-2.5):1, preferably (1.6-2.1):1, based on the molar number of isocyanate groups to the molar number of active hydrogen atoms; wherein the active hydrogen atoms refer to hydrogen atoms that can react with isocyanate groups.

[0022] Preferably, in component B1), the mass ratio of polyether polyol 1, polyether polyol 2 and polyether polyol 3 is (20-70):(0-10):(5-50), preferably (35-55):(0-5):(15-35).

[0023] In some preferred embodiments, the isocyanate component is selected from polyisocyanates, preferably polyphenylmethane polyisocyanate, more preferably one or more of Wanhua Chemical WANNATE 82681, Wanhua Chemical WANNATE PM-8215, Huntsman 5005, Covestro 44V20, and BASF M20S; polyphenylmethane polyisocyanate is an isocyanate compound well known in the art, and its technical information can refer to Section 1.2 of the Handbook of Polyurethane Raw Materials and Additives (edited by Liu Yijun) published by Chemical Industry Press.

[0024] Preferably, the molecular weight of the polyether polyol 1 is 200-600;

[0025] Preferably, the molecular weight of the polyether polyol 2 is 1000-8000;

[0026] Preferably, the molecular weight of the polyether polyol 3 is 300-1000.

[0027] The above polyether polyols can be obtained through commercial purchase or prepared by methods commonly used in the art. The functionality of the polyether polyol refers to the functionality of the initiator, such as the initiator of the polyether polyol with a functionality of 2 can be selected from ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 1,2-pentanediol, hexanediol, diethylene glycol, triethylene glycol, dipropylene glycol, diethylene glycol, neopentyl glycol, etc.; the initiator of the polyether polyol with a functionality of 3 can be selected from glycerol, trimethylolpropane, triisopropanolamine, etc.

[0028] In some preferred embodiments, the fused ring amines are selected from one or more of 1,5-diaminonaphthalene, 1,4-diaminoanthraquinone, 1,3,6,8-tetraaminopyrene, 2,3-diaminonaphthalene, and 1,8-diaminonaphthalene.

[0029] In some preferred embodiments, component B) further includes B5) a small molecule alcohol with a functionality of 1-4, preferably 2-3; the small molecule alcohol is preferably one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 1,2-pentanediol, hexanediol, diethylene glycol, triethylene glycol, dipropylene glycol, diethylene glycol, neopentyl glycol, glycerol, and trimethylolpropane.

[0030] In some preferred embodiments, component B) further includes B6) a catalyst; the catalyst is selected from an organometallic catalyst and / or an amine catalyst, more preferably one or more of triethylamine, tributylamine, triethylenediamine, tetramethyl-ethylenediamine, pentamethyldiethylene-triamine, N,N-methylaniline, N,N-dimethylaniline, stannous octoate, stannous oleate, tin laurate, dimethyltin dilaurate, dibutyltin dilaurate, dibutyltin dithiolate, bismuth bismuth salt, bismuth bismuth salt, and bismuth cyclopentaneate.

[0031] In some preferred embodiments, component B) further comprises a blowing agent; the blowing agent is selected from physical blowing agents and / or chemical blowing agents, preferably one or more of water, halogenated hydrocarbons, and hydrocarbon compounds; the amount of blowing agent used generally depends on the requirements of the polyurethane foam density.

[0032] Preferably, the halogenated hydrocarbon is one or more of monochlorodifluoromethane, dichloromonofluoromethane, dichlorofluoromethane, and trichlorofluoromethane;

[0033] Preferably, the hydrocarbon compound is one or more of butane, pentane, cyclopentane, hexane, cyclohexane and heptane.

[0034] In some preferred embodiments, component B) further comprises one or more of a surfactant, an antioxidant, a dispersant, an anti-hydrolysis agent, an antistatic agent, a viscosity reducer, a crosslinking agent, an internal mold release agent, a flame retardant, a pigment, a filler, a foaming stabilizer, and a light stabilizer.

[0035] The surfactants include but are not limited to organosilicon, polyols, silicones, sulfonated fatty alcohols, sulfonated fatty acids and other nonionic surfactants.

[0036] As a preferred formulation, component B) contains the following substances based on the total mass of 100%:

[0037] Condensed ring amines 0.3-2%, preferably 0.5-1.2%;

[0038] Polyether polyol 1 20-70%, preferably 35-55%;

[0039] Polyether polyol 2 0-10%, preferably 0-5%;

[0040] Polyether polyol 3 5-50%, preferably 15-35%;

[0041] Small molecule alcohol 5-35%, preferably 10-26%;

[0042] Catalyst 0-1%, preferably 0.1-0.5%;

[0043] Foaming agent 0-1.5%, preferably 0.5-1%;

[0044] Surfactant 0-3%, preferably 0.8-2%.

[0045] The polyurethane composition of the present invention can quickly pre-crosslink and chain extend in the early stage of the reaction through compounding of a specific isocyanate component and an isocyanate reactive component, thereby achieving high thixotropy, having a relatively high viscosity under no-pressure conditions, and having an excellent sag effect; the viscosity is greatly reduced under a certain pressure condition, and excellent fluidity can be maintained at room temperature, while excellent fluidity is also achieved under high temperature conditions; the foam prepared from the polyurethane composition and the interlayer material prepared from the foam have excellent surface quality and mechanical properties.

[0046] As a method for preparing a highly thixotropic polyurethane composition foam as described above, the present invention further provides, in a preferred embodiment, the isocyanate component and the isocyanate reactive component are uniformly mixed by a polyurethane foaming machine, and the mixed raw materials are poured into a mold, and the main steps include:

[0047] Mix the isocyanate components uniformly at a temperature of 10-45°C;

[0048] Mixing the isocyanate reactive components uniformly at a temperature of 10-45°C;

[0049] The isocyanate component and the isocyanate reactive component are uniformly mixed by a high pressure machine, and the mixture is poured into a mold. The polyurethane composition foams, expands, and fills in the mold. The mold temperature is controlled at 80-130°C for curing. After 1-5 minutes of complete curing, the mold is cooled and the material is taken out to obtain the polyurethane composition foam.

[0050] The present invention also provides a use of the highly thixotropic polyurethane composition as described above in automobile sandwich materials and composite materials.

[0051] The polyurethane composition can be sprayed on the surface of the sandwich material for use. The sandwich material comprises a sandwich layer and a reinforcement layer, wherein the sandwich layer includes but is not limited to one or more of foam material, paper honeycomb, metal honeycomb, and plastic honeycomb; and the reinforcement layer includes but is not limited to one or more of glass fiber, carbon fiber, metal fiber, natural fiber, aramid fiber, and polyethylene fiber.

[0052] As a preparation method of the sandwich material further provided by the present invention, in a preferred embodiment, a paper honeycomb is used as a core material, and a glass fiber mat is used as a reinforcing layer on both sides of the core material; the isocyanate component and the isocyanate reactive component are uniformly mixed by a polyurethane foaming machine, and the mixed raw materials are sprayed on one side of the glass fiber mat, the fixture is turned over, and the operation of spraying the other side is repeated until the double-sided spraying is completed, and the sandwich product is placed in a mold; the main steps include:

[0053] Mix the isocyanate components uniformly at a temperature of 10-45°C;

[0054] Mixing the isocyanate reactive components uniformly at a temperature of 10-45°C;

[0055] The isocyanate component and the isocyanate reactive component are uniformly mixed by a polyurethane foaming machine, and the mixture is sprayed on both sides of the glass fiber mat. The polyurethane composition is leveled, foamed, and expanded in the gap between the glass fiber mat and the paper honeycomb to produce a polyurethane foam to fill the cavity of the sandwich material. The mold temperature is controlled at 100-130°C for curing. After 1-2 minutes of complete curing, the product is taken out to form a polyurethane composition sandwich material.

[0056] The invention provides a highly thixotropic polyurethane composition. After an isocyanate component and an isocyanate reactive component are mixed, high thixotropy can be quickly achieved. Under no-pressure conditions, the viscosity is relatively high (apparently non-flowing) and excellent sag effect is achieved. When the product enters a mold and is subjected to a certain pressure, the viscosity can be greatly reduced, and the fluidity can be maintained for a long time at room temperature and high temperature, promoting surface leveling. An interlayer material prepared from the polyurethane composition has high surface density, excellent filling effect, high aesthetics and excellent mechanical properties. The polyurethane composition is particularly suitable for preparing interlayer materials with complex shapes and large sizes. DETAILED DESCRIPTION

[0057] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.

[0058] The main raw material information used in the following examples and comparative examples of the present invention is as follows:

[0059] Isocyanate component: WANNATE 82681, NCO content 31.5wt%, Wanhua Chemical;

[0060] Isocyanate component: Huntsman 5005, NCO content 31.1wt%, Huntsman;

[0061] Isocyanate component: Covestro 44V20, NCO content 31.4wt%, Covestro;

[0062] 1,5-Diaminonaphthalene, commercially available;

[0063] 1,4-Diaminoanthraquinone, commercially available;

[0064] 1,3,6,8-Tetraaminopyrene, commercially available;

[0065] DETDA, diethyltoluenediamine, commercially available;

[0066] Polyether polyol 1-1, starting with glycerol, hydroxyl value of 600 mgKOH / g, polymerization of propylene oxide and ethylene oxide, ethylene oxide content of 95%, based on the total mass of propylene oxide and ethylene oxide;

[0067] Polyether polyol 1-2, glycerol starting material, hydroxyl value of 450 mgKOH / g, polymerization of propylene oxide and ethylene oxide, ethylene oxide content of 65%, based on the total mass of propylene oxide and ethylene oxide;

[0068] Polyether polyol 2-1, pentaerythritol starting material, hydroxyl value of 110 mgKOH / g, polymerization of propylene oxide and ethylene oxide, ethylene oxide content of 5%, based on the total mass of propylene oxide and ethylene oxide;

[0069] Polyether polyol 2-2, glycerol starting material, hydroxyl value of 65 mgKOH / g, polymerization of propylene oxide and ethylene oxide, ethylene oxide content of 15%, based on the total mass of propylene oxide and ethylene oxide;

[0070] Polyether polyol 2-3, glycerol starting, hydroxyl value 24mgKOH / g, propylene oxide and ethylene oxide polymerization, ethylene oxide content 12%, based on the total mass of propylene oxide and ethylene oxide;

[0071] Polyether polyol 3-1, propylene glycol initiator, hydroxyl value 280 mgKOH / g, propylene oxide polymerization;

[0072] Polyether polyol 3-2, glycerol initiator, hydroxyl value 490 mgKOH / g, propylene oxide polymerization;

[0073] Glycerol (GL), diethylene glycol (DEG), commercially available;

[0074] Surfactants: B8002, B8715, Evonik Specialty Chemicals (Shanghai) Co., Ltd.;

[0075] Catalyst 1: KC152, purchased from Wanhua Chemical;

[0076] Catalyst 2: SA102, purchased from Air Chemicals, Inc., USA;

[0077] Foaming agent: water.

[0078] The main test methods or standards used for the polyurethane composition or its foam in the following examples and comparative examples of the present invention are as follows:

[0079] Viscosity test standard: GB / T 12008.7-2010; Take 100g of polyurethane composition, control the raw material temperature at 25±1℃, put it in a 500ml paper cup, adjust the speed as required, mix for 10 seconds and immediately conduct actual viscosity test at different speeds; turn the polyurethane composition upside down vertically to observe the apparent fluidity; evaluate thixotropy by actual viscosity and apparent fluidity;

[0080] Evaluation of raw material sagging: Take 100g of the polyurethane composition, control the raw material temperature at 25±1℃, put it in a 500ml paper cup, rotate at 3000r / min, mix according to the proportion for 10 seconds, then immediately turn the paper cup upside down vertically, restart the timing, and record the mass of the polyurethane composition flowing out of the paper cup within 20 seconds;

[0081] High temperature fluidity evaluation: The raw material temperature is controlled at 25±1°C, 10 g of the uniformly mixed polyurethane composition is taken and placed in a circular mold with a diameter of 8 cm and a thickness of 2 mm. The mold temperature is 110°C, and the flowable time of the polyurethane composition is detected with a glass rod;

[0082] The main test methods or standards used for the sandwich products prepared by the polyurethane compositions in the examples and comparative examples are as follows:

[0083] Product density test standard: GB / T 6343;

[0084] Compression strength test standard: GB / T 8813-2020;

[0085] Tensile strength test standard: GB / T 528-2009;

[0086] Bending strength test standard: GB / T 8812-2007;

[0087] Impact strength test standard: GB / T 1043-2008;

[0088] Product sag evaluation: The total weight of raw materials dripping during the flipping process of the sandwich product is calculated as M. When M≤5g, the sag effect is excellent; 5<M≤50g, the sag effect is average; M>50g, the sag effect is poor;

[0089] Product surface density evaluation: Honeycomb paper sandwich products at 100cm 2The number of pits with a diameter of 0.5 mm and above is the evaluation standard; when the number of pits is ≤5, the surface density of the product is excellent; 5<the number of pits≤15, the surface density of the product is general; 15<the number of pits≤30, the surface density of the product is poor; the number of pits>30, the surface density of the product is extremely poor;

[0090] Evaluation of product surface filling effect: The size of honeycomb paper sandwich products is 1.5m*1.5m*2cm, and the area of ​​missing material on the upper and lower surfaces and edges of the products is used as the evaluation standard; when the missing material area is ≤3cm 2 , the surface filling effect of the product is excellent; 3cm 2 <Shortage area≤10cm 2 , the surface filling effect of the product is general; 10cm 2 <Shortage area≤30cm 2 The surface filling effect of the product is poor; the missing area is > 30cm 2 , the surface filling effect of the product is extremely poor.

[0091] The amounts of the components of the polyurethane compositions in the examples and comparative examples of the present invention are listed in Table 1, in parts by mass.

[0092] Table 1

[0093]

[0094]

[0095] Referring to the formula in Table 1, the raw materials of the polyurethane composition in each embodiment and comparative example were prepared respectively. The isocyanate component and the isocyanate reactive component were uniformly mixed using a polyurethane foaming machine; a paper honeycomb structure was used as the core material, with a thickness of 2 cm and a size of 1.5 m*1.5 m, and glass fiber mats were used on both sides of the core material, and the surface density of the glass fiber mat was 450 g / m 2 ; and spray the mixed polyurethane raw material on one side of the glass fiber mat (0.55 kg of polyurethane raw material is sprayed on one side per square meter), turn the fixture over, repeat the operation to spray the other side until the double-sided spraying is completed, and put the sandwich product into the mold. The polyurethane composition is leveled, foamed, and expanded in the gap between the glass fiber mat and the paper honeycomb to produce a polyurethane foam to fill the cavity of the sandwich material. The mold temperature is controlled at 100-130°C for curing. After 1-2 minutes of complete curing, the product is taken out to form a polyurethane composition sandwich product.

[0096] The surface density, surface filling effect and mechanical properties of the polyurethane composite sandwich product were tested, and the results are listed in Table 2.

[0097] Table 2

[0098]

[0099] From the comparison between Table 1 and Table 2 above, we can see that:

[0100] Comparative Example 1 and Comparative Example 1 show that when the polyurethane composition does not contain condensed cyclic amines, the thickening and thixotropic effects of the product are very poor, and the raw material sagging effect is very poor, resulting in extremely poor surface density and surface filling effects of the final product;

[0101] Comparative Example 3 and Comparative Example 2 show that when DETDA, a commonly used compound on the market, is used instead of condensed ring amines, the thickening and anti-drip effects of the product are very good, but the thixotropy is poor, the viscosity decreases slowly with increasing shear, the product has poor fluidity when under pressure in the mold, and the high-temperature flow time is too short, resulting in poor surface density and filling effect of the final product;

[0102] Comparative Example 1 and Comparative Example 3 show that when the amount of polyether polyol 2 exceeds 10%, the polyurethane composition cannot be properly formed due to the difference in reaction activity, and the thickening effect and thixotropic effect of the polyurethane composition are poor; resulting in extremely poor surface density of the product, and poor surface filling effect of the product;

[0103] Comparative Example 6 and Comparative Example 4 show that when the amount of polyether polyol 1 is less than 20%, the polyurethane composition has too little high-activity polyether content, resulting in no obvious thickening and thixotropic effect of the polyurethane composition, and thus poor anti-drip effect, resulting in poor surface density and filling effect of the product.

[0104] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A highly thixotropic polyurethane composition, characterized in that: It comprises: A) an isocyanate component, B) an isocyanate-reactive component; Wherein, component B) comprises the following composition: B1) fused cyclic amines having a functionality of 1-6, preferably 2-4; B2) polyether polyol 1, having a functionality of 2-5, preferably 3-4, a hydroxyl value of 200-800 mgKOH / g, preferably 400-700 mgKOH / g, and an ethylene oxide content of 20-100%, preferably 60-100%, in the polymerized monomers, based on the total mass of propylene oxide and ethylene oxide; Optionally B3) polyether polyol 2, with a functionality of 2-4, a hydroxyl value of 20-170 mgKOH / g, and an ethylene oxide content of 0-20%, based on the total mass of propylene oxide and ethylene oxide; Optionally B4) polyether polyol 3, prepared by polymerization of propylene oxide, with a functionality of 2-4 and a hydroxyl value of 150-600 mgKOH / g, preferably 240-500 mgKOH / g.

2. The highly thixotropic polyurethane composition according to claim 1, characterized in that The usage ratio of component A) to component B) is (1.5-2.5):1, preferably (1.6-2.1):1, based on the molar number of isocyanate groups to the molar number of active hydrogen atoms; Preferably, in component B1), the mass ratio of polyether polyol 1, polyether polyol 2 and polyether polyol 3 is (20-70):(0-10):(5-50), preferably (35-55):(0-5):(15-35).

3. The highly thixotropic polyurethane composition according to claim 1, characterized in that: The isocyanate component is selected from polyisocyanate, preferably polyphenylmethane polyisocyanate, more preferably one or more of Wanhua Chemical WANNATE 82681, Wanhua Chemical WANNATE PM-8215, Huntsman 5005, Covestro 44V20, and BASF M20S; Preferably, the molecular weight of the polyether polyol 1 is 200-600; Preferably, the molecular weight of the polyether polyol 2 is 1000-8000; Preferably, the molecular weight of the polyether polyol 3 is 300-1000.

4. The highly thixotropic polyurethane composition according to any one of claims 1 to 3, characterized in that: The condensed ring amines are selected from one or more of 1,5-diaminonaphthalene, 1,4-diaminoanthraquinone, 1,3,6,8-tetraaminopyrene, 2,3-diaminonaphthalene and 1,8-diaminonaphthalene.

5. The highly thixotropic polyurethane composition according to any one of claims 1 to 4, characterized in that: Component B) further comprises B5) a small molecule alcohol having a functionality of 1-4, preferably 2-3; the small molecule alcohol is preferably one or more of ethylene glycol, propylene glycol, 1,4-butanediol, 1,3-butanediol, 1,2-butanediol, 1,2-pentanediol, hexanediol, diethylene glycol, triethylene glycol, dipropylene glycol, diethylene glycol, neopentyl glycol, glycerol, and trimethylolpropane.

6. The highly thixotropic polyurethane composition according to any one of claims 1 to 5, characterized in that: Component B) further includes B6) a catalyst; the catalyst is selected from an organometallic catalyst and / or an amine catalyst, more preferably one or more of triethylamine, tributylamine, triethylenediamine, tetramethyl-ethylenediamine, pentamethyldiethylene-triamine, N,N-methylaniline, N,N-dimethylaniline, stannous octoate, stannous oleate, tin laurate, dimethyltin dilaurate, dibutyltin dilaurate, dibutyltin dithiolate, bismuth bismuth salt, bismuth bismuth salt, and bismuth cyclopentaneate.

7. The highly thixotropic polyurethane composition according to any one of claims 1 to 6, characterized in that: Component B) further comprises a blowing agent; the blowing agent is selected from a physical blowing agent and / or a chemical blowing agent, preferably one or more of water, halogenated hydrocarbons, and hydrocarbon compounds; Preferably, the halogenated hydrocarbon is one or more of monochlorodifluoromethane, dichloromonofluoromethane, dichlorofluoromethane, and trichlorofluoromethane; Preferably, the hydrocarbon compound is one or more of butane, pentane, cyclopentane, hexane, cyclohexane and heptane.

8. The highly thixotropic polyurethane composition according to any one of claims 1 to 7, characterized in that: Component B) further comprises one or more of a surfactant, an antioxidant, a dispersant, an anti-hydrolysis agent, an antistatic agent, a viscosity reducer, a crosslinking agent, an internal mold release agent, a flame retardant, a pigment, a filler, a foaming stabilizer, and a light stabilizer.

9. The highly thixotropic polyurethane composition according to any one of claims 1 to 8, characterized in that: Component B) contains the following substances based on the total mass of 100%: Condensed ring amines 0.3-2%, preferably 0.5-1.2%; Polyether polyol 1 20-70%, preferably 35-55%; Polyether polyol 2 0-10%, preferably 0-5%; Polyether polyol 3 5-50%, preferably 15-35%; Small molecule alcohol 5-35%, preferably 10-26%; Catalyst 0-1%, preferably 0.1-0.5%; Foaming agent 0-1.5%, preferably 0.5-1%; Surfactant 0-3%, preferably 0.8-2%.

10. Use of the highly thixotropic polyurethane composition according to any one of claims 1 to 9 in automotive sandwich materials and composite materials.

Citation Information

Patent Citations

  • Polyurethane system for the production of polyurethane sandwich parts

    CN101641384B

  • Polyurethane ureas prepared using diaminoanthraquinones as chain lengthening agents and a process for the preparation of the polyurethane ureas

    CA2037183A1

  • PU (polyurethane) doped MBBR (moving bed biofilm reactor) filler composition as well as preparation method and application thereof

    CN117756272A

  • Adhesive composition

    US5508111A

  • AU483580B2